Об аподизации в оптических телескопах - Прокофьев, В.К.; Лебедева, В.В.; Орлов, М.И.; Соколовский, Р.И. (Кинематика и физика небесных тел, 1988)
Найдены функции зрачка, решающие следующую задачу аподизации: максимальная концентрация энергии к центру геометрического изображения светящейся точки. Интенсивности боковых колец в изображении точки для данных функций зрачка резко уменьшены по сравнению с обычным дифракционным распределением. Рассмотрена задача аподизации, связанная с увеличением разрешения. Проведен анализ функций зрачка, позволяющих улучшить разрешение по сравнению с критерием Рэлея. Установлено, что для функций зрачка, не изменяющих знака, увеличение разрешения не превышает 1.6. Для функций зрачка с одним скачком фазы, равным π, фактически достижимо такое же улучшение разрешения. Для реализации рассмотренных способов улучшения качества изображения можно проводить соответствующую коррекцию частотноконтрастной характеристики (ЧКХ) в канале регистрации сигнала. To solve the apodization problem i. e. to obtain maximum energy concentration in the centre of geometrical image of a light point the pupil functions were found. Generally, these functions are expressed through linear combinations of Bessel functions of the first and second kind. The intensities of side rings in the point image for these pupil functions are sharply decreased as compared to conventional diffraction distribution. The problem of apodization associated with the increase of resolution is considered. The pupil functions which make it possible to improve the resolution as compared with Rayleigh criterion are analysed. It is found that for pupil functions with a constant sign the increase of resolution does not exceed 1.6. For the pupil functions with one phase discontinuity π the same improvement of resolution is also attainable. To apply the considered methods of seeing improvement it is possible to make appropriate correction in the channel of signal registration.